Global Imperative of Suicidal Ideation in 10 Countries Amid the COVID-19 Pandemic - Cheung, Teris; Lam, Simon Ching; Lee, Paul Hong; Xiang, Yu Tao; Yip, Paul Siu Fai; , The International Research Collaboration on COVID-19 (Frontiers in Psychiatry, 2021)
Background: The novel coronavirus (COVID-19) has had a detrimental impact on individuals' psychological well-being; however, a multi-country comparison on the prevalence of suicidal ideation due to the virus is still lacking. Objectives: To examine the prevalence and correlates of suicidal ideation among the general population across 10 countries during the COVID-19 pandemic. Materials and methods: This was a cross-sectional study which used convenience sampling and collected data by conducting an online survey. Participants were sourced from 10 Eastern and Western countries. The Patient Health Questionnaire (PHQ-9) was used to measure the outcome variable of suicidal ideation. Ordinal regression analysis was used to identify significant predictors associated with suicidal ideation. Results: A total of 25,053 participants (22.7% male) were recruited. Results from the analysis showed that the UK and Brazil had the lowest odds of suicidal ideation compared to Macau (p < 0.05). Furthermore, younger age, male, married, and differences in health beliefs were significantly associated with suicidal ideation (p < 0.05). Conclusions: The findings highlight the need for joint international collaboration to formulate effective suicide prevention strategies in a timely manner and the need to implement online mental health promotion platforms. In doing so, the potential global rising death rates by suicide during the pandemic can be reduced.